Factors Affecting the Behavior of Pregnant Women toward Avoiding Polluted Air - Somayeh Pormosayebi; Mohsen Shamsi; Mahboobeh Khorsandi; Ali Koolivand; Mehdi Ranjbaran (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Pregnant women are highly vulnerable to air pollution, which has a significant impact on the health of the pregnant women and their fetus. Objective: The present study aimed at determining the factors affecting the behavior of pregnant women in Arak, Iran toward avoiding exposure to polluted air. Materials and Methods: In this analytic cross-sectional study, 208 pregnant women who were referred to health centers in Arak city were selected using multistage random sampling method. The data was collected by a researcher-made questionnaire, completed after determining its validity and reliability. This questionnaire included demographic characteristics of the mother, knowledge and the behavior of some of the mothers toward avoiding exposure to polluted air, and was scored on 100 points. Data were analyzed using Pearson and Spearman correlation coefficients, one-way analysis of variance (ANOVA) and T-test. Results: The mean age of mothers was 26.48 ± 4.77 years, mean gestational age was 14.88 ± 5.9 weeks, and mean knowledge score was 40.56 ± 16.91. There was a positive and significant correlation between knowledge and mother s age (r = 0.279), husband s age (r = 0.222), and number of smokers in the family (r = 0.178) and a negative and significant correlation with gestational age (r = -0.168) (p = 0.05). Also, there was a significant association between educational level of mother and husband, husband s job and income with knowledge and behavior (p = 0.05). Conclusion: According to the results of this study, mothers knowledge was less than average. It is thus suggested to develop and implement educational programs for pregnant women advanced in age and during the end of pregnancy to improve their behavior toward avoiding polluted air.